Engaging With Patient Online Health Information Use: A Survey of Primary Health Care Nurses. (4th September 2014) - Gilmour, Jean; Hanna, Sue; Chan, Helen; Strong, Alison; Huntington, Annette
Internet health information is used by patients for health care decision making. Research indicates this information is not necessarily disclosed in interactions with health professionals. This study investigated primary health care nurses' engagement with patient online health information use along with the respondents' disclosure of online sources to their personal health care provider. A questionnaire was posted to a random sample of 1, 000 New Zealand nurses with 630 responses. Half the respondents assessed patients' online use ( n = 324) and had encountered patients who had wrongly interpreted information. Health information quality evaluation activities with patients indicated the need for nursing information literacy skills. A majority of respondents (71%, n = 443) used online sources for personal health information needs; 36.3% ( n = 155) of the respondents using online sources did not tell their personal health care provider about information obtained. This study identifies that there are gaps in supporting patient use but more nursing engagement with online sources when compared with earlier studies.